The effect of root orientation on inferior alveolar nerve injury after extraction of impacted mandibular third molars based on propensity score-matched analysis: a retrospective cohort study - Shijun Kuang; Yuhao Liu; Weijie Zhuang; Kechen Li; Wenbin Yang; Yihong Tian (BMC Oral Health, 2023)
Abstract Background The injury of the inferior alveolar nerve (IAN) is one of the most serious complications of impacted mandibular third molars (IMTMs) extraction. The influence of the root orientation of IMTMs on IAN injury is still controversial. A deeper understanding of the risk factors of IAN injury conduces to better prevention of IAN injury. This study aims to explore whether root orientation is an independent risk factor of IAN injury during IMTMs extraction using the statistical strategy of propensity score matching (PSM). Methods This retrospective cohort study included 379 patients with 539 cases of high-risk IMTMs screened by panoramic radiography and cone beam computed tomography. The IAN injury incidence after extraction of different groups of IMTMs was analyzed using the chi-square test or Fisher’s exact test. The correlation between third molar root orientation and impaction depth/contact degree with IAN was evaluated by the Lambda coefficient. Based on PSM for balancing confounding factors including age, sex, impaction depth, and contact degree, the effect of root orientation on the incidence of IAN injury was further analyzed using Fisher’s exact test. Results There were significant group differences in IAN injury incidence in impaction depth, root orientation, and contact degree of root-IAC before PSM. Root orientation was correlated with impaction depth and contact degree of root-IAC. After PSM, there were 9 cases with IAN injury and 257 cases without IAN injury. There were significant group differences between the buccal and non-buccal groups after PSM, and the risk of IAN injury was higher when the root was located on the buccal side of IAC (OR = 8.448, RR = 8). Conclusions Root orientation is an independent risk factor of IAN injury, and the risk is higher when the root is located on the buccal side of IAC. These findings could help better evaluate the risk of inferior alveolar nerve injury before the extraction of IMTMs.